2012
DOI: 10.1097/ta.0b013e31823d0f35
|View full text |Cite
|
Sign up to set email alerts
|

Initial hematocrit in trauma

Abstract: Admission Hct correlates with signs of shock and hemorrhage in trauma patients requiring emergency surgery because fluid shifts rapidly from the interstitial space into the vasculature. This finding of a rapid Hct change contradicts the current teaching in most trauma textbooks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 15 publications
1
20
0
1
Order By: Relevance
“…The role of the Hct level, however, is more controversial, with the traditional standpoint of Hct being a more sensitive indicator of acute blood loss than the Hb. The shift of fluid from the interstitial into the intravascular space in the physiological response to blood loss is thought to occur at a more rapid rate, making this parameter more useful over a shorter period of time20). Our data, however, suggests the Hct tends to derange in correlation with the Hb concentration, which is in keeping with the findings of the analysis performed on a large series of trauma patients confirming identical behavior of these particular parameters21).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The role of the Hct level, however, is more controversial, with the traditional standpoint of Hct being a more sensitive indicator of acute blood loss than the Hb. The shift of fluid from the interstitial into the intravascular space in the physiological response to blood loss is thought to occur at a more rapid rate, making this parameter more useful over a shorter period of time20). Our data, however, suggests the Hct tends to derange in correlation with the Hb concentration, which is in keeping with the findings of the analysis performed on a large series of trauma patients confirming identical behavior of these particular parameters21).…”
Section: Discussionsupporting
confidence: 88%
“…In this context, the Hb concentration is generally deemed to be inaccurate at defining the degree of acute blood loss20,21). The role of the Hct level, however, is more controversial, with the traditional standpoint of Hct being a more sensitive indicator of acute blood loss than the Hb.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study of 196 trauma patients, Ryan et al . [117] found that Hct at admission closely correlates with haemorrhagic shock. However, this study included severe cases requiring emergency surgery only (most with penetrating injuries), and may not be applicable to the general trauma patient population.…”
Section: Resultsmentioning
confidence: 99%
“…Ryan et al retrospectively reviewed admission hematocrit (HCT) with the need for transfusion and vasopressor support among trauma patients requiring emergency surgery. The authors found that in this cohort of patients admission HCT as low as 37 % was predictive of the need for additional hemodynamic support [86]. Interestingly, they found that traditional markers of shock, including pulse and respiratory rate, were not predictors for necessitating further hemodynamic support.…”
Section: Blood Productsmentioning
confidence: 81%